2016
DOI: 10.1111/1460-6984.12226
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the educational and social needs of children with language impairment or autism spectrum disorder: the parents’ perspectives

Abstract: Although previous research indicates that parents of children with ASD are overrepresented among those who express dissatisfaction with the provision made to meet their child's needs, this study indicates high levels of satisfaction and overlap between the perspectives of parents of children with LI or ASD regarding their child's educational progress and their own involvement in decision-making about the child's provision. The findings indicate the importance for policy and practice of focusing on identified n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 35 publications
4
39
2
1
Order By: Relevance
“…Importantly, teachers in our study noted that the stress and adversarial nature of the transition process for some children, and the anxiety this caused the family, exacerbated the children's difficulties adjusting to their new school. New legislation in England, which states that parents should have greater choice and control when choosing a secondary school for their child (UK Department for Education, 2014) offers some hope towards potentially reducing at least some of the stress and uncertainty for parents (see Lindsay et al, 2016, for parents' views on their involvement in decision making), although future research is necessary to determine the potential benefits of the new legislative context. It is also possible that school placement problems may have a disproportionate effect on families of autistic children compared to children with other SEN, given that autism is one of the most frequently named disabilities for consideration at SENDIST (see Tissot, 2011), although this possibility again warrants further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, teachers in our study noted that the stress and adversarial nature of the transition process for some children, and the anxiety this caused the family, exacerbated the children's difficulties adjusting to their new school. New legislation in England, which states that parents should have greater choice and control when choosing a secondary school for their child (UK Department for Education, 2014) offers some hope towards potentially reducing at least some of the stress and uncertainty for parents (see Lindsay et al, 2016, for parents' views on their involvement in decision making), although future research is necessary to determine the potential benefits of the new legislative context. It is also possible that school placement problems may have a disproportionate effect on families of autistic children compared to children with other SEN, given that autism is one of the most frequently named disabilities for consideration at SENDIST (see Tissot, 2011), although this possibility again warrants further examination.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in all levels examined scores for the extent of PI were high, except the level of decisionmaking, which received a score that was much lower than the other levels (ibid). In contrast, Lindsay et al (2016) found that most parents were satisfied with their involvement in decision-making processes with regard to their children's entitlement to receive special education services. It appears that PI differs from case to case and from one disability to another.…”
Section: Involvement Of Parents Of Children With Snmentioning
confidence: 77%
“…Mand argued instead that children with behavioural problems need help in both systems. Correspondingly, Lindsay et al's () large‐scale interview study in England of the views of parents of children with language impairment (LI) or ASD highlighted that the quality of provision matters rather than the location per se. However, they concluded that parents whose child was included individually in mainstream were less positive about provision than those parents whose child attended a mainstream school with specialist resourced provision.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, research highlighting the benefits and challenges faced by special schools is investigated (Hornby & Witte, 2008;Parsons et al, 2009;Parsons, 2015;Day et al, 2012;Reed et al, 2012;Kelly et al, 2014;Black, 2014;Cook et al, 2016). Thirdly, research emphasising the value and challenges of inclusion in mainstream settings is reviewed (Frederickson et al, 2007;Lindsay et al, 2016;O'Hagan & Hebron, 2016;Broomhead, 2013Broomhead, , 2014de Graaf et al, 2013;Waddington & Reed, 2016;de Boer et al, 2013;Glazzard, 2014;Webster & Blatchford, 2015). Research that listens to the voice of 'disabled' and 'non-disabled' children regarding mainstream and special school provision is the final theme (Griffiths, 2007;Prunty et al, 2012;Gasson et al, 2015;Geordiadi et al, 2012;Tuersley-Dixon & Frederickson, 2016;Roberts & Simpson, 2016;Feiler, 2013;Skovlund, 2014).…”
mentioning
confidence: 99%